Senior business consultant project: Giving advice while gaining other awareness and career competency. Issue 2 (17th February 2023) - Vander Schee, Brian A.; Andrews, Demetra; Stovall, Tony
Abstract: Grounded in self-expansion theory, the Senior Business Consultant Project addresses the gap between career competencies possessed by business graduates and those expected by employers. The project took place in a virtual environment to mirror future business settings. Fourth-year consulting students worked in teams of two to provide guidance to first-year client students in teams of four to eight on a month-long team project. The project was implemented at a Midwest public university. Analysis of efficacy results suggest senior students found the collaborative project to be novel and exciting, fostering their sense of their own capabilities, other awareness, and career competencies.